2021
DOI: 10.1038/s41467-021-23974-4
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-specific collaborative transcription factor networks are promoted by OCT4 in the progression of prostate cancer

Abstract: Interactive networks of transcription factors (TFs) have critical roles in epigenetic and gene regulation for cancer progression. It is required to clarify underlying mechanisms for transcriptional activation through concerted efforts of TFs. Here, we show the essential role of disease phase-specific TF collaboration changes in advanced prostate cancer (PC). Investigation of the transcriptome in castration-resistant PC (CRPC) revealed OCT4 as a key TF in the disease pathology. OCT4 confers epigenetic changes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…On the other hand, OCT1 is widely expressed, including in the placenta, rectum and testis (Human Protein Atlas available from http://www.proteinatlas.org ), in the human body among the eight OCT proteins, and known to be associated with the master regulator of pluripotency, octamer-binding transcription factor 4 (OCT4), in stem cells 28 30 . We recently reported that OCT4 associates with Nuclear Respiratory Factor 1 (NRF1) in AR-negative PC and consists an important component of the TF complex in CRPC 31 . Interestingly, OCT1 binding sites were enriched in a series of genes that are regulated by MYC in MYC-driven lung adenocarcinomas 32 , suggesting that OCT1 and MYC may co-regulate a series of androgen-responsive genes in PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, OCT1 is widely expressed, including in the placenta, rectum and testis (Human Protein Atlas available from http://www.proteinatlas.org ), in the human body among the eight OCT proteins, and known to be associated with the master regulator of pluripotency, octamer-binding transcription factor 4 (OCT4), in stem cells 28 30 . We recently reported that OCT4 associates with Nuclear Respiratory Factor 1 (NRF1) in AR-negative PC and consists an important component of the TF complex in CRPC 31 . Interestingly, OCT1 binding sites were enriched in a series of genes that are regulated by MYC in MYC-driven lung adenocarcinomas 32 , suggesting that OCT1 and MYC may co-regulate a series of androgen-responsive genes in PC.…”
Section: Discussionmentioning
confidence: 99%
“…LNCaP, 22RV1, PC3 are cultured using RPMI-1640 and DU145 using DMEM medium, respectively, and both are supplemented with 10% FBS, 50 U/mL penicillin and 50 μg/mL streptomycin, in addition, some of LNCaP and 22Rv1 cells are treated with 100 nM of dihydrotestosterone (DHT) (Wako, Tokyo, Japan) for 3 days 14 . Short tandem repeat (STR) analysis was performed to authenticate the cell lines used in the present study 31 , 42 . Also, these cells have been checked for Mycoplasma contamination using real-time PCR performed by Funakoshi Co., Ltd. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The androgen receptor (AR) plays a crucial role in the pathogenesis of PCa and is considered a clinically validated target for the treatment of PCa ( 41 44 ). Unfortunately, long-term androgen deprivation can ultimately lead to castration-resistant PCa (CRPC), which favors metastasis and poor prognosis ( 45 47 ). Although much effort has been made to improve PCa treatment, it is still needed to identify more sensitive biomarkers to guide early diagnosis and treatment ( 37 , 48 , 49 ).…”
Section: The Tumor-suppressor Role Of Draic In Cancersmentioning
confidence: 99%
“…Among them, Nrf1 is identified as an evolutionarily conserved transcription activator that binds to GC-rich DNA elements in promoters of a host of nuclear genes encoding proteins involved in mitochondrial structure and functions [ 11 , 12 , 13 , 14 , 15 ]. Multiple studies using ChIP-seq analysis have identified distinct sets of Nrf1’s target genes in different cell types, suggesting that Nrf1 acts in a context-dependent manner in regulating cell growth, differentiation, and mitochondrial biogenesis [ 16 , 17 , 18 , 19 ]. In addition, Nrf1 interacts with other proteins involved in different cellular functions.…”
Section: Introductionmentioning
confidence: 99%